Transformational retailing and the emergence of a modern brand: Liberty of London, 1875–1900. Issue 2 (3rd May 2020) - Alexander, Nicholas; Doherty, Anne Marie; Cronin, James
ABSTRACT: This article considers the role of a transformational retail setting in the development of an iconic brand identity in the last quarter of the nineteenth century. The focus of this research is Liberty of London. Through experiential engagement and augmented admission, Liberty created a retail environment that challenged existing practices. Coupled with the development of a brand identity enhanced through authoritative advocacy and consumers' allegorical encounters with the firm's core brand message, Liberty achieved the symbolic substantiation of a distinct taste regime through the market-mediation of authenticity. We discuss how brand representation in a transformational retail setting in the metropolitan market of the late nineteenth century legitimised and structured consumer expectations in a context of growing middle class demand for merchandise with enhanced aesthetic qualities and associated lifestyle values.